Designing an Interprofessional, Student-Led Clinic with the Patient-Centered Medical Home (PCMH) Model - Claire Leighton; Grayson Jackson; Tanner Israel; Joanna Chyu; Dayoung Jeon; Christopher Garcia (Journal of Student-Run Clinics, 2022)
Students and faculty at the University of Texas Medical Branch (UTMB) embarked on the novel undertaking of establishing a comprehensive, interprofessional clinic treating underserved, uninsured residents of Galveston County, Texas, and the surrounding area, modeled after the patient-centered medical home (PCMH). The need for such a community clinic is evident in relevant literature and patients’ suggestions, in addition to local demographic data. The comprehensive nature of this approach to clinic design is apparent in the intricate planning and documents produced by the steering committee, which outline a unique operational structure that optimizes clinic flow. This paper describes the planning, implementation, and future directions of an interprofessional, student-led free clinic operating under the PCMH model that offers a framework for other clinics.